2001
DOI: 10.1093/carcin/22.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of 2-amino-1-methyl-6-phenylimidazo (4,5-b)pyridine(PhIP)-induced mutations within the Apc gene of rat colon

Abstract: A large proportion of human cancers result from exposure of individuals to environmental or occupational carcinogens. The early detection of carcinogen-induced mutations is a prerequisite for the identification of individuals at risk for developing cancer. Short G-rich repetitive sequences have been previously identified as hot-spots for frameshift mutagenesis induced by a large variety of carcinogens belonging to several families of widespread environmental pollutants. In order to test if these sequences, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous studies using different models established several potential mechanism of PhIP‐induced carcinogenesis. Using cultured cells and rats, it was found that PhIP metabolite attacks DNA, forms dG‐C8‐PhIP adduct, and subsequently induces G to C mutation or G deletion, which was suggested to result in the expression of truncated APC protein or dominant active mutant Ctnnb1 and lead to the activation of Wnt signaling . Notably, a ‐1G deletion in a G stretch such as 5'‐GGGA‐3' in Apc gene was found in 4 out of 8 PhIP‐induced F344 rat colon tumors causing reading frame shift and truncation .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using different models established several potential mechanism of PhIP‐induced carcinogenesis. Using cultured cells and rats, it was found that PhIP metabolite attacks DNA, forms dG‐C8‐PhIP adduct, and subsequently induces G to C mutation or G deletion, which was suggested to result in the expression of truncated APC protein or dominant active mutant Ctnnb1 and lead to the activation of Wnt signaling . Notably, a ‐1G deletion in a G stretch such as 5'‐GGGA‐3' in Apc gene was found in 4 out of 8 PhIP‐induced F344 rat colon tumors causing reading frame shift and truncation .…”
Section: Discussionmentioning
confidence: 99%
“…heterocyclic aromatic amines, HCA) may remain quite a long time in direct contact with the epithelial cells in the distal colon and rectum mucosa prior to evacuation, thus facilitating the uptake of these compounds in this particular part of the gastrointestinal tract. Furthermore, it has been shown that male rats fed 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP), the most abundant HCA in cooked meat, develop colon tumours, in which specific-1G mutations within 5 0 -GGGA-3 0 sequences of the APC gene were detected [39,40]. Moreover, the same authors suggested that these specific mutations could be useful for mutational fingerprinting of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…BHP is, in addition, associated with mutations of ␤-catenin phosphorylation sites in the same model system (70). In contrast, the carcinogenic amine 2-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine, associated with cooked meats, caused Apc mutations with as little as 1 wk of exposure in rats (10). In our experiments, nuclear localization of ␤-catenin appeared to be associated with the progression, rather than the initiation, of alachlor-induced olfactory neoplasms, as nuclear localization of ␤-catenin was not found in early lesions.…”
Section: Discussionmentioning
confidence: 99%